Mga kagamitang panturo para sa isahang paglinang ng mga kasanayan sa pakikinig (aural discourse) ng mga mag-aaral sa unang taon ng mataas na paaralan - Pangilinan, Luisa Sunga 1937- (1978)
This seminar paper attempted to present the design and development phases in the preparation of aural discourse materials. A survey was made and examination of instructional materials currently available in Pilipino for first year high school students was done so as to have a valid justification for the design of a new set of materials. The experimental materials were subjected to an internal evaluation to determine the workability of the materials in actual classroom situations.
Vita.
Thesis (M.A.T Pilipino sa Kagilirang Pambansang Wika)--University of the Philippines, Diliman.
Keywords: Listening -- Study and teaching (Secondary) -- Philippines; Teaching -- Philippines -- Aids and devices